Kegilaan Dan Peradaban di Madura (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2022)
This paper aims to determine the model of handling schizophrenia mental disorders carried out by Islamic Boarding Schools in Madura and Yogyakarta. The research method used is qualitative. The result is a qualitative description of the treatment of mental disorders carried out by Islamic boarding schools in Madura and Yogyakarta. The results showed that the treatment of mental disorders in Madura and Yogyakarta is to carry out rehabilitation with a psychoreligious approach.